Efficiency of the Electronic License Plate Recognition Systems - Slapsinskas, P.; Zilys, M. (Elektronika ir Elektrotechnika, 2013)
The precise recognition of the vehicle determines the efficiency of intelligent transportation systems. Intelligent transportation systems become more effective if it can identify the vehicle. Electronic license plate recognition systems used to solve this problem. Proposed electronic license plate recognition systems model adapted for simple internet protocol video surveillance cameras. An analysis of the internet protocol video surveillance camera‘s processors, operating principle and software created guidelines for the algorithm. According to performance of the internet protocol video surveillance camera formed four efficiency criteria for license plate recognition algorithms. It’s performed the experiment with four algorithms to search for a license number plate by different attributes of the license number. The most efficient algorithm was selected by criteria from experimental results. The algorithm is further analyzed and proposed the application model of the internet protocol video surveillance camera. DOI: http://dx.doi.org/10.5755/j01.eee.19.8.5396